Handling Low and High Demand Mode on Safety Instrumented Function - Totok R. Biyanto; Franky Kusuma; Hendra Cordova; Yerry Sutatio; Ridho Bayuaji (Institute of Advanced Engineering and Science, 2015)
In this paper, demand rate and hazardous event frequency considerations which effect to the error on the SIL calculation will be discused. The various value of hazardous event frequency and demand rate will be evaluated in this paper. The result of this paper is when hazardous event frequency 10E-06/year and PFD’s safeguard 0.00002, with test interval 1 year, the SILs of low and high demand start showing different level at demand 5.1/year. At that point, we shouldn’t use simplified formula for low demand, because it will make different SIL with the exponential formula and simplified high demand formula. The requared SIL targets are SIL 2 and SIL 1, for exponential formula and simplified high demand formula, respectifely. Hence, it should be taken more attention and consideration for various value of hazardous event frequency with various demand rate.